(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the level of satisfaction of work environments at the administrative body of the dimensions: organizational justice, relationship with superiors, respect and appreciation of efforts, job promotion, credibility of officials, detection of the level of job integration, and identify the differences for the variables of satisfaction of work environments and job integration attributed to the variables: age, academic qualification, years of experience, and clarify the correlation between satisfaction of work environments and job integration, and the study relied on the descriptive correlational approachA questionnaire was applied to a sample of (256) from the administrative body (males and females) at King Khalid University, and the results resulted: that the level of satisfaction of work environments came by (64%), its practice is medium, and job integration is provided by (76%) for the sample members on average, and there is an inverse correlation between the variables of satisfaction of work environments and job integration, after credibility ranked first in terms of its ability to achieve Integration, then after respect ranked second, and the relationship with superiors ranked third, and after promotion ranked fourth, and there are statistically significant differences between the satisfaction of work environments and job integration attributed to the variable of gender in favor of males and the educational qualification and age, and the absence of differences for the variable years of experience for positive happiness, and years of experience and age for job absorption.